2018
DOI: 10.1111/1471-0528.15413
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic incisional negative pressure wound therapy reduces the risk of surgical site infection after caesarean section in obese women: a pragmatic randomised clinical trial

Abstract: RCT: prophylactic incisional NPWT versus standard dressings postcaesarean in 876 women significantly reduces the risk of SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 33 publications
6
97
1
Order By: Relevance
“…[11][12][13] We recently carried out a multicentre randomised controlled trial (RCT) that evaluated the effectiveness of prophylactic iNPWT in obese women (body mass index; BMI ≥30kg/m 2 ) delivering by caesarean section. 14 This study demonstrated that prophylactic iNPWT statistically significantly halved the risk of SSI compared with standard postoperative dressings after CS (RR 0.50, 95% CI 0.30-0.84; P=0.007). Some decision-analytic modelling studies of iNPWT used on abdominal surgical incisions suggests that iNPWT may lower hospital or healthcare costs in obese patients at high risk of SSI.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…[11][12][13] We recently carried out a multicentre randomised controlled trial (RCT) that evaluated the effectiveness of prophylactic iNPWT in obese women (body mass index; BMI ≥30kg/m 2 ) delivering by caesarean section. 14 This study demonstrated that prophylactic iNPWT statistically significantly halved the risk of SSI compared with standard postoperative dressings after CS (RR 0.50, 95% CI 0.30-0.84; P=0.007). Some decision-analytic modelling studies of iNPWT used on abdominal surgical incisions suggests that iNPWT may lower hospital or healthcare costs in obese patients at high risk of SSI.…”
Section: Introductionmentioning
confidence: 66%
“…Details of the RCT have been reported elsewhere. 14 In brief, the trial was performed in two tertiary, and three teaching hospitals in Denmark from 2013 to 2016. Overall, 876 women with a pre-pregnancy BMI of ≥30 kg/m 2 who had an emergency or planned CS were randomised to iNPWT (n=432) or a standard postoperative dressing (n=444) and followed for 30 days post-CS.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the indications for NPWT have expanded to include the management of high-output exudate and seromas by employing it as an alternative method to closed suction draining. 8 In our unit, a modified two-layer negative pressure wound therapy (2-LNPWT) dressing in combination with a standard negative pressure dressing system [Renasys Go, Smith & Nephew, UK] has routinely been employed as a standard of care to manage inguinal lymphadenectomy wounds postoperatively by the senior author (MM). The rationale for employing the 2-LNPWT technique is that it acts as a traditional closed-suction drainage (CSD) system whilst simultaneously applying continuous external compression to the skin and the wound cavity deep to it.…”
mentioning
confidence: 99%
“…However, the results of randomized controlled trials have been mixed. A randomized trial of iNPWT in obese patients undergoing cesarean reported a reduction in SSI rates [23]. Another randomized trial of elective and urgent general surgery patients showed lower rates of SSI with iNPWT, but patients with dirty wounds, BMI > 40, and ASA > III were excluded [24].…”
Section: Discussionmentioning
confidence: 99%